Implementation of the Living Qur'an Concept in School Education: A Literature Review - Muhammad Rasyid Ridho (Al-Fadlan: Journal of Islamic Education and Teaching, 2025)
This study aims to analyze the implementation of the Living Qur’an concept in school education through a systematic literature review. The Living Qur’an concept emphasizes the internalization of Qur’anic values into the daily lives of students, going beyond mere memorization or textual understanding. The literature reveals that the success of Living Qur’an implementation is strongly influenced by the habituation of religious activities such as Qur’an recitation (tadarus), congregational prayers, and Qur’anic literacy, all of which effectively foster students’ religiosity and strong character. Teacher professionalism and exemplary conduct are central factors, positioning teachers as facilitators, motivators, and role models in this process, further supported by digital innovations such as the E-Rapor Qur’an application, which enhances monitoring and evaluation of learning. Furthermore, synergy among schools, families, and the broader social environment is crucial to holistically strengthen the internalization of Qur’anic values. However, challenges remain, including limited infrastructure, insufficient environmental support, and an overemphasis on rote memorization. This research recommends strengthening teacher capacity, developing technology-based learning innovations, and fostering active multi-stakeholder collaboration as key strategies. Thus, the Living Qur’an concept can be optimized as a model for character education that is adaptive and relevant to contemporary educational demands, shaping morally upright, Qur’anic-minded generations ready to face global challenges in the digital era.